Popular religion in Russia: 'double belief' and the making of an academic myth - Rock, Stella (Routledge studies in the history of Russia and Eastern Europe, 2007)
Christian idol-worshippers and 'pagan survivals' -- Heretics, doubters and 'wrong-believing' -- A history of historians -- How Russian is 'double-belief'?